Body Mass Index Trajectories and Duration of Obesity in Thai Children Diagnosed with Hypertension - Witchuri Paksi B.N.S; Suthatip Sirijunpen M.D; Pracha Nuntnarumit M.D; Kwanchai Pirojsakul M.D (SAGE Publishing, 2021)
This study explored the relationship between BMI trajectories and the duration of obesity in Thai children diagnosed with hypertension. Demographic and blood pressure data from 536 children (270 boys, 50.3%) from a school in Bangkok, Thailand were collected. Hypertension was defined as blood pressure above the cutoff values specified in the 2017 American Academy of Pediatrics guidelines on 3 occasions. Records of BMI over the previous 3 years were reviewed. The prevalence of hypertension was 2.61% (14/536). Complete data on BMI trajectories were available in 421 non-hypertensive and 12 hypertensive children. The increase in BMI z-score over the previous 3 years was significantly greater in the hypertensive group than the non-hypertensive group, 1.45 (95% CI 0.42 to 1.88) versus 0.09 (95% CI: −0.35, 0.65), P  = .008. In conclusion, children with a confirmed diagnosis of hypertension had a greater increase in BMI over the past 3 years than non-hypertensive children.